Modern ultrasound methods and atherosclerosis assessment in patients with familial hypercholesterolemia - A. I. Ershova; A. N. Meshkov; S. A. Boytsov; T. V. Balakhonova (Кардиоваскулярная терапия и профилактика, 2011)
Familial hypercholesterolemia (FHCH) is characterised by early atherosclerosis development and its fast progression. The prevalence of FHCH inRussiahas been increasing, therefore, it is important to evaluate the potential of various methods for atherosclerosis diagnostics. Arterial ultrasound is an informative, accessible, and safe method for evaluating atherosclerotic vascular changes. The modern ultrasound methods allow describing vascular wall status in detail, including qualitative and quantitative characteristics of its structure and function. At the same time, most ultrasound characteristics of arterial wall are used in research settings or are under development, and not implemented into clinical practice. The most promising parameters, applicable for clinical use in FHCH patients, simultaneously describe atherosclerosis severity and its localization, such as total plaque height, ankle-brachial index, and plaque number.